Penegakkan Hukum Pidana Atas Penganiayaan Bersama Antar Geng Motor Di Kabupaten Subang - Putri Megantara; Sri Nurcahyani (CV. ULIL ALBAB CORP, 2025)
The Unitary State of the Republic of Indonesia is a state governed by law, as stated in Article 1, paragraph (3) of the 1945 Constitution. Law, as a binding regulation, aims to create justice, certainty, and benefit in society. In the context of criminal law, these rules regulate prohibited or mandatory actions, with sanctions for violators. The enforcement of criminal law aims to protect individual rights and establish social order. One frequently occurring issue is violence by motorcycle gangs, such as assault, which is regulated under Article 170 of the Indonesian Criminal Code (KUHP). The case of Bayu Prasetyo and Ramdan Maulana highlights the fatal consequences of mob violence, resulting in the victim's death. Legal enforcement is essential to protect society and uphold justice